2005
DOI: 10.1262/jrd.17029
|View full text |Cite
|
Sign up to set email alerts
|

Estrogen Inhibits Interleukin-18 mRNA Expression in the Mouse Uterus

Abstract: Abstract. ) is a proinflammatory cytokine expressed in female reproductive organs in humans, rats and mice. The physiological roles of uterine IL-18 and the regulatory mechanisms of IL-18 gene expression are unclear. The present study aimed to clarify the effects of estradiol-17β (E2) and progesterone (P4) on IL-18 mRNA expression in the mouse uterus. Distribution and expression levels of IL-18 mRNA were studied using an RNase protection assay. Expression of IL-18 mRNA was observed in all organs studied, inclu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
11
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 39 publications
(47 reference statements)
4
11
0
Order By: Relevance
“…18Rβ subunits, which constitute functional IL-18 receptors, is highly probable in uteri, although we did not analyze the expression of IL-18Rα and IL-18Rβ proteins. We recently demonstrated that IL-18 mRNA is present in mouse uteri [10,11]. Taken together, these observations suggest the presence of the IL-18 system in the mouse uterus.…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…18Rβ subunits, which constitute functional IL-18 receptors, is highly probable in uteri, although we did not analyze the expression of IL-18Rα and IL-18Rβ proteins. We recently demonstrated that IL-18 mRNA is present in mouse uteri [10,11]. Taken together, these observations suggest the presence of the IL-18 system in the mouse uterus.…”
Section: Discussionmentioning
confidence: 55%
“…These findings indicate that IL-18Rα gene expression is regulated by estrogen and progesterone. Our previous study also revealed that IL-18 mRNA expression was decreased by estrogen and progesterone [11]. Therefore, it is possible that the physiological actions of IL-18 may be inhibited by sex steroid hormones, and IL-18 may exert its actions under the conditions of low circulating levels of steroid hormones.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Hormonal administration as a consequence of ovarian hyperstimulation will increase the cytokine depletion, since endometrial exposure to a high concentration of oestrogens significantly decreases endometrial IL-18 expression (Ledee et al, 2006). A negative impact of oestrogens on IL-18 expression has been also reported in mice and pigs (Ashworth et al, 2010;Murakami et al, 2005).…”
Section: The Role Of Endometrial Tumor Necrosis Factor-like Weak Indumentioning
confidence: 99%
“…In addition, it has been reported that estrogens prevent the expression of IL-18 in mouse uterus. 17) On the other hand, we also found that excessive IFN-γ via IL-18 results in cataract development. 18,19) From these reports, it is possible that IL-18 levels are also increased in the lenses of postmenopausal women, and that enhanced IFN-γ via IL-18 may lead to the formation and progression of cataracts.…”
mentioning
confidence: 52%